Strength and microstructure of eco-concrete produced using waste glass as partial and complete replacement for sand. Issue 1 (1st January 2018) - Olofinnade, Oluwarotimi M.; Ede, Anthony N.; Ndambuki, Julius M.; Ngene, Ben U.; Akinwumi, Isaac I.; Ofuyatan, Olatokunbo
Abstract: The sustainable benefits of waste glass usage in concrete include the possibility of reducing solid waste and greenhouse gas emission and preservation of raw materials. This current study examines the effect of recycled waste glass as a partial and complete substitute for natural sand in producing eco-friendly concrete. The recycled waste glass was proportioned in levels of 25, 50, 75 and 100% by weight to substitute sand in the concrete using a mix ratio of 1:2:4 (cement:sand:gravel) at a W/C ratio of 0.5 targeting 20 MPa strength at 28 days. Tests, which include X-ray fluorescence (XRF), were conducted on the waste glass and cement materials; slump test was performed on the freshly prepare concrete at different percentage glass content. Compressive and tensile strength tests were performed on 60 specimens after 3, 7, 28 and 90 days of curing. The concrete microstructure was examined using the scanning electron microscope (SEM). Results showed that workability and the mechanical strength of the concrete produced decreased with increasing waste glass content. However, concrete containing 25% and 50% waste glass contents showed significant enhancement in strength, but it is recommended that the optimum glass content should be 25% for the production of sustainable eco-concrete.